THE IMPLEMENTATION OF THEMATIC PROGRESSION PATTERNS WITH COOPERATIVE LEARNING MODEL (TP-CL) IN IMPROVING WRITING SKILLS - -, Farikah (Language Circle: Journal of Language and Literature, 2012)
This article examines the effect of Thematic Progression Patterns with Cooperative Learning Method (TP-CL) on the improvement of the students’ writing skills and the teaching- learning activities of writing courses. This classroom action research was conducted in the English Department of Magelang Tidar University in the academic year of 2011/2012. The subjects were fourth semester students who took the course of Writing III. To analyze the results of writing tests and the effectiveness of the teaching and learning activities Brown’ and Bailey’s theory (1984) was used. The results show that the implementation of Thematic Progression Patterns with Cooperative Learning Method (TP-CL) improves the writing skills of the students. In addition, the application of this model can create effective teaching-learning activities. The results suggest that lecturers teaching writing courses should introduce Thematic Progression Patterns to the students in order that they can write paragraphs coherently and organize various themes neatly in order that they can write the paragraph artistically.